Scientific Literacy in physics Curriculum change has not been enough - Nélida Valdivia Lillo (Corporación Universitaria Minuto de Dios, 2016)
Based on the problems shown in Chile due to the poor performance of students on international tests as well as a low level of Scientific Literacy (hereafter AC), it was sought to contrast elements, supporting the research in a constructivist approach, integrating a qualitative and quantitative approach in three fundamental areas of education: Curriculum using the technique of content analysis, teachers through the interview and students with a test, getting with the latter to confirm the degree of A.C. in physics of the students under study. The results of the instruments, allowed to recognize the importance that acquires the A.C. at Ministerial level in Chile, but the dissonance expressed by teachers, allows us to establish a reference in the teaching and learning processes, and consequently of the low levels of A.C. in physics, in the studied areas that this research has revealed.